(untitled) (Journal of Partial Differential Equations, 2003)
" In this paper, the perturbed higher-order NLS equation with periodic boundary condition is considered. The existence of the homoclinic orbits for the truncation equation is established by Melnikov analysis and geometric singular perturbation theory."